Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s10815-005-9010-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oxidative Stress on Outcomes of Assisted Reproductive Techniques

Abstract: Malondialdehyde can be used as a marker of oxidative stress and a potential marker in predicting assisted reproductive techniques outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 15 publications
2
35
2
2
Order By: Relevance
“…While several studies reported a positive correlation between FF ROS level and pregnancy rate following an IVF treatment [6,7], others found either no correlation [8,9], or demonstrated a negative correlation between ROS levels and reproductive functions [10][11][12]. We believe that this inconsistency derived from the different study methodology, which examine ROS from different FF sources, i.e.…”
Section: Introductionmentioning
confidence: 93%
“…While several studies reported a positive correlation between FF ROS level and pregnancy rate following an IVF treatment [6,7], others found either no correlation [8,9], or demonstrated a negative correlation between ROS levels and reproductive functions [10][11][12]. We believe that this inconsistency derived from the different study methodology, which examine ROS from different FF sources, i.e.…”
Section: Introductionmentioning
confidence: 93%
“…Uncontrolled and excessive production of ROS, however, appears to have a significant role as one of the major factors leading to an infertile status (Agarwal et al, 2003. The role of ROS and antioxidants in relation to female reproductive function has, in contrast, received relatively little attention, although there is some evidence of both physiological and pathological effects (Attaran et al, 2000;Pasqualotto et al, 2004;Das et al, 2006;Oral et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The results of a study by Pasqualotto et al (14) showed parallel results, as pregnant women after IVF treatment had higher lipid peroxidation (LPO) products compared to nonpregnant women. However, Oral et al (12) found no significant relationship between follicular fluid malondialdehyde levels and fertilization rates. Accordingly, Jozwick et al (29) reported no significant correlation between IVF outcome and different oxidative stress marker concentrations.…”
Section: Discussionmentioning
confidence: 97%
“…It is found in high concentrations in the cytoplasm, nucleus and mitochondria (11). Oxidative stress is believed to affect reproductive functions (12). The effect of oxidative stress on the reproductive potential of men has been investigated extensively worldwide.…”
Section: Introductionmentioning
confidence: 99%